Does Auditing Impact the Quality of Information on Corporate Sustainability Report: Empirical Evidence from Vietnamese Businesses - Viet, Nguyen Vu; Lien, Vu Thi Phuong; Anh, Phi Thi Kieu (Journal of Ecohumanism, 2024)
The world business community is moving very strongly towards the Net Zero goal on the sustainable business journey. Vietnamese businesses cannot stand out of this race. Facing the requirements of green development and sustainable development, the business community needs to redefine its success, which now does not just lie in financial numbers, but businesses need to connect their long-term success and growth to bring sustainable benefits to the community, society and the environment. Standards of revenue, profit, shareholder benefits or financial numbers are no longer the only measure of business success, but have now expanded the ability to adapt, withstand and recover. before unprecedented formulas in money. Only when balancing the three-legged crown: economy - society - environment can businesses succeed in today's era. This study was conducted to evaluate the factors affecting the process of preparing and publishing sustainable development reports of businesses, on that basis to clarify the role of auditing in this process, from It provides recommendations to improve the quality of published information, and promote the sustainable development of businesses.